The Effects of Smartphone Use on Students’ Spiritual and Moral Perspectives - Muhammad Alwan Nursuhaida (Universitas Pendidikan Ganesha, 2025)
The widespread use of smartphones has raised concerns about their influence on students’ spiritual and moral development. This study aims to analyze the relationship between smartphone use and students’ spiritual attitudes and moral perspectives. The research employed a quantitative approach with a correlational design. The study involved 118 students selected as respondents. Data were collected through a structured questionnaire designed to measure the intensity of smartphone use, spiritual attitudes, and moral perspectives. Data analysis was carried out using statistical techniques with Excel software. The findings revealed that smartphone use had no significant effect on students’ spiritual attitudes (p > 0.05). In contrast, the analysis of moral perspectives indicated a measurable effect, yet it remained neutral, showing neither a clear positive nor negative correlation. The study concludes that religious and moral education plays a more dominant role in shaping students’ spiritual and moral dimensions compared to smartphone use. These findings highlight the importance of strengthening spiritual and moral education programs and promoting the meaningful use of technology as a strategy to support the ethical and spiritual growth of students.